RELIABILITY AND VALIDITY OF BECK DEPRESSION INVENTORY AMONG GENERAL POPULATION IN KHYBER PAKHTUNKHWA, PAKISTAN - Khan, Aftab Alam; Marwat, Salim Khan; Noor, Muhammad Munir; Fatima, Saniya (Journal of Ayub Medical College Abbottabad, 2015)
Background: Beck Depression Inventory is frequently used for assessing depression across different cultures. Despite widely application of Beck Depression Inventory, there is surprisingly lack of empirical research on psychometric validation of this scale in Pakistan. In this regard the current study has determined the reliability and validity of Beck Depression Inventory in Pakistan. Methods: Urdu version Beck Depression Inventory was administration to 250 Inpatient and Outpatient Department visitors in Ayub Teaching Hospital, Abbottabad, Khyber Pakhtunkhwa, Pakistan. Initially reliability was determined and later on validly analysis was done. Results: The reliability results show that Cronbach alphas ranged from 0.75 to 0.92, whereas inter-item correlations ranged from 0.53 to 0.78. The validity analysis show that factor loadings for all items of Beck Depression Inventory ranged from 0.77 to 0.93. Furthermore, the two subscales presented good model fit indices, thus conforming its construct validity. Conclusion: The results of current study show that Beck Depression Inventory has good psychometric properties followed by its administration to general population in Khyber Pakhtunkhwa, Pakistan; therefore this scale could be effectively used for assessing depression in Pakistan